Case reportA case of acute brachial artery occlusion after transradial coronary intervention - Sang, Zhenchi; Jin, Huigen; Liu, Zongjun (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Artery occlusion can be a complication of transradial coronary angiography or intervention. Radial artery occlusion was usual with an incidence of 2-18% in the literature [1-4], which should in theory not endanger the viability of the hand because of double blood supply. In contrast, brachial artery occlusion was not reported, but can result in acute hand ischemia, even necrosis. Transcatheter thrombolysis was effective and safe, and can be used to recanalize the artery occlusion [5, 6]. The article first discusses transcatheter thrombolysis; it was effective and safe in the condition of acute brachial artery thrombosis after transradial intervention.